The Impact of Islamic Values and Local Wisdom on Students' Social Behavior: A Study at Pondok Pesantren Al-Fatimah, Bojonegoro - Nanang Setiawan; Monica Resavita; Lintang Auliya Sasmita (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
Islamic values and local wisdom are integral to shaping individuals' social behavior, particularly within the educational framework of Pondok Pesantren (Islamic boarding schools). This study focuses on analyzing the impact of these values on the social behavior of students at Pondok Pesantren Al-Fatimah Bojonegoro. Employing a quantitative approach, the research gathered data through questionnaires distributed to a total of 306 students, ensuring a comprehensive overview of their experiences and perceptions. The findings reveal a significant correlation between the implementation of Islamic values and local wisdom and the positive social behavior exhibited by the students. This research not only enhances academic literacy on the subject but also provides empirical evidence underscoring the critical role these elements play in character formation. The insights gained from this study can inform pesantren management, guiding them in the development of more effective educational programs aimed at fostering character development in students. Ultimately, the study advocates for a holistic educational approach that integrates religious teachings with cultural values, thereby contributing to the personal and social growth of Santri in their communities